Enhancing learning and retention through the distribution of practice repetitions across multiple sessions. - Walsh, Matthew M.; Krusmark, Michael A.; Jastrembski, Tiffany; Hansen, Devon A.; Honn, Kimberly A.; Gunzelmann, Glenn (Memory & Cognition, 2023)
The acquisition and retention of knowledge is affected by a multitude of factors including amount of practice, elapsed time since practice occurred, and the temporal distribution of practice. The third factor, temporal distribution of practice, is at the heart of research on the spacing effect. This research has consistently shown that separating practice repetitions by a delay slows acquisition but enhances retention. The current study addresses an empirical gap in the spacing effects literature. Namely, how does the allocation of a fixed number of practice repetitions among multiple sessions impact learning and retention? To address this question, we examined participants' acquisition and retention of declarative knowledge given different study schedules in which the number of practice repetitions increased, decreased, or remained constant across multiple acquisition sessions. The primary result was that retention depended strongly on the total number of sessions in which an item appeared, but not on how practice repetitions were distributed among those sessions. This outcome was consistent with predictions from a computational cognitive model of skill acquisition and retention called the Predictive Performance Equation (PPE). The success of the model in accounting for the patterns of performance across a large set of study schedules suggests that it can be used to tame the complexity of the design space and to identify schedules to enhance knowledge acquisition and retention.